Pengaruh Faktor Keamanan dan Kemudahan terhadap Minat Generasi Millennial Menggunakan Mobile Banking - Nita Amanda; Muhammad Nazieh Ibadillah (STEBI Global Mulia Cikarang, 2023)
In this era of rapidly developing technology, it can attract the interest of customers who are used as supporting facilities, where customers prioritize aspects of security and ease of use. Mobile banking technology is a type of service provided by banks to their customers so that customers can carry out banking transactions anytime and anywhere at any time without having to come to the bank concerned. The objectives of the problem in this study are: (1) To determine the influence of Islamic bank mobile banking security on the interest of the millennial generation. (2) To find out the effect of the convenience of Islamic bank mobile banking on the interest of the millennial generation. (3) To find out the influence of the security and convenience of Islamic bank mobile banking together on the interest of the millennial generation. This study uses the theory of Jarvenpaa and Hua as the X_1 variable of security, Davis and Jogiyanto's theory as the X_2 variable of convenience and Sardiman's theory as the Y variable of interest. The method used in this research is a quantitative approach. Data collection techniques in this study used documentation and questionnaires with a Likert scale. The sampling technique used was using the Slovin formula with the number of samples used in this study as many as 100 respondents. Furthermore, the questionnaire data were analyzed using multiple linear regression analysis, validity test, reliability test, classical assumption test including multicollinearity test, normality test, heteroscedasticity test, t test, F test and coefficient of determination test. The results showed that the security variable had a partially significant effect on the millennial generation's interest in using mobile banking with a t-count of 3.693 > 1.660 t-table (df=97). And the convenience variable significantly influences the millennial generation's interest in using mobile banking with a t count of 3.666 > 1.660 t table (df=97). Next, the simultaneous effect with the F test shows that the security and convenience variables together significantly influence the millennial generation's interest in using mobile banking with an calculated F value of 12.120 > 2.76 F table.